The Prevalence and Ultrasonographic Features of Ectopic Pregnancy, Rawalpindi, Pakistan - Idrees, Nimra; Rehman, Aqsa; Nabi, Sadikun; Niaz, Mehwish; Stanikzai, Hashmatullah; Syed, Hina; Hanif, Anam; Husnain, Ali (Indus Journal of Bioscience Research, 2025)
Background: Ectopic pregnancy (EP) continues to be a major contributor to maternal morbidity and mortality throughout early gestation. Early detection using ultrasonography is crucial for effective therapy and optimal outcomes. Objective: To find out the prevalence and ultrasonographic characteristics of ectopic pregnancy in patients exhibiting early pregnancy problems. Materials and Methods: This cross-sectional study was performed at Health Ways Diagnostic Centre and Life Care Lab in Rawalpindi, Pakistan, from April 2024 to September 2024. One hundred fifty (150) women aged 20-40 years with suspected early pregnancy problems underwent transvaginal and/or transabdominal ultrasonography. Data on clinical presentation, β-hCG levels, and sonographic findings were gathered and analyzed utilizing SPSS and GraphPad Prism. Results: In a study of 150 women, 29 cases of ectopic pregnancy were identified, resulting in a prevalence rate of 19.3% (95% CI: 13.8–26.4%). Tubal pregnancies constituted 96.6% of cases, whereas non-tubal pregnancies represented only 3.4% (p < 0.01). The predominant age group of patients was 31–35 years, comprising 36.7% of the sample, with the majority of diagnoses made before 9 weeks of gestation. The primary risk factors identified were intrauterine device use (34%), prior ectopic pregnancy (34.4%), and tubal surgery (17%). The predominant ultrasonographic finding was an empty uterus accompanied by an adnexal mass (48.3%), followed by an adnexal mass with free fluid (27.6%) and the hyperechoic ring sign (17.2%). The classic tubal ring was identified in merely 6.9% of instances. Conclusion: This study concludes that ectopic pregnancy predominantly originates in the fallopian tubes and is frequently linked to risk factors, including the use of intrauterine devices (IUDs) and previous tubal surgeries. Transvaginal ultrasonography is essential for early and precise diagnosis.